THEORETICAL FRAMEWORK: IMPACT OF ELECTRONIC MARKETING ON CUSTOMER RELATIONSHIPS ON SOCIAL MEDIA - Ali Fadhil Al Yousfe (Scholars Digest Publishing, 2025)
This study aims to explore the impact of e-marketing on the mutual relationships between customers and brands via social media, with a focus on how to enhance interaction, trust and loyalty, A quantitative research methodology was used based on an electronic questionnaire distributed to a sample of 150 participants, including consumers, e-marketing professionals and academic experts, The data was analyzed using statistical tools such as Cronbach's alpha coefficient and exploratory factor analysis to ensure the reliability and validity of the results". "The results showed that active interaction with customers via social media significantly enhances their satisfaction, with a satisfaction rate of 85% among participants who reported high interaction, The results also showed that trust plays a pivotal role in enhancing customer loyalty, with loyalty reaching 90% among participants who reported high trust in the brand In addition, the study confirmed that the speed of response to customer inquiries is a key factor in improving their experience, with a satisfaction rate of 88% among participants who received a quick response, This study provides valuable insights for companies seeking to improve their social media marketing strategies, highlighting challenges related to privacy and data management, It also offers practical recommendations for enhancing engagement, trust, and loyalty between brands and customers in the rapidly evolving digital environment".